Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1021/la804043z
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Assembly from Achiral Rod−Coil Molecules Triggered by Compression at the Air−Water Interface

Abstract: A series of achiral rod-coil molecules consisting of an oligo(p-phenylene) conjugated rod with a poly(ethylene oxide) or poly(propylene oxide) coil laterally attached through an imidazole linkage were synthesized, and their interfacial behaviors were investigated. Compounds 1a and 1b have a similar surface behavior with a shoulder indicating a transformation of rod segments from flat-on to vertical orientation. Interestingly, CD and AFM suggest chiral films are formed when the LB films were deposited after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 65 publications
1
39
0
Order By: Relevance
“…Generally, the basic requirement for such applications are,- a perfectly organized molecular thin films having specific properties, careful alignment of the molecules and a substrate which have very good stability with respect to thermal and chemical changes. Langmuir-Blodgett (LB) technique is a powerful tool in creating carefully controlled supramolecular structures of organized molecular assemblies [27, 28, 29, 30, 31, 32], which have their potential applications in above mentioned areas. By changing different film forming parameters during LB film formation, it is possible to control the bulk properties of the materials that were incorporated into the LB films.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the basic requirement for such applications are,- a perfectly organized molecular thin films having specific properties, careful alignment of the molecules and a substrate which have very good stability with respect to thermal and chemical changes. Langmuir-Blodgett (LB) technique is a powerful tool in creating carefully controlled supramolecular structures of organized molecular assemblies [27, 28, 29, 30, 31, 32], which have their potential applications in above mentioned areas. By changing different film forming parameters during LB film formation, it is possible to control the bulk properties of the materials that were incorporated into the LB films.…”
Section: Introductionmentioning
confidence: 99%
“…These applications require, in general, well ordered films consisting of molecules with specific properties, carefully aligned with respect to each other and the substrates possessing high degree of stability to thermal and chemical changes. Langmuir-Blodgett (LB) technique is a powerful tool in creating carefully controlled supramolecular structures of organized molecular assemblies [24][25][26][27][28][29] , which have their potential applications in above mentioned areas. The bulk properties of the materials incorporated into LB films can be controlled by the organization of molecules in the films and also by changing various LB parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the chirality on a surface can also be created by achiral molecules, [28][29][30][31][32][33] which lead to point chirality or organisational chirality. 34 The first one results from the absorbing of achiral molecules in such a way that the molecular and surface reflection symmetry are destroyed.…”
Section: Chiral Molecular Assemblies On Achiral Surfacesmentioning
confidence: 99%
“…Although strongly related to intrinsic molecular chirality, it is not necessary that all components bear a chiral site (presence of an asymmetric center). [11,20,21] Indeed, it has been demonstrated that it is possible to attain supramolecular chirality by combining chiral molecules with achiral ones or even with exclusively achiral ones. [22][23][24] However, to achieve such results strong intermolecular interactions must occur between the components, such as Hbonds, electrostatic or hydrophobic interactions, -stacking, among others.…”
Section: Introductionmentioning
confidence: 99%